AN ANALYSIS OF TEACHERS’ UNDERSTANDING OF ENGLISH SYLLABUS (ATP) IN MERDEKA CURRICULUM AT JUNIOR HIGH SCHOOL - Makkaraeng, Fitria Wahyu; Tahir, Muhammad; Korompot, Chairil Anwar (State University of Makassar, 2024)
This study aims to determine teachers' understanding of the flow of learning objectives (Alur Tujuan Pembelajaran/ATP) after participating in the Merdeka Curriculum training. Researcher apply qualitative methods. Participants in this study were 2 English teachers. Data collection was carried out through interviews and document analysis of the flow of learning objectives (Alur Tujuan Pembelajaran/ATP). Based on the results of the in-depth interviews, the data results show that the participants has a higher understanding of the components and indicators contained in the flow of learning objectives (Alur Tujuan Pembelajaran/ATP). In addition, teachers are greatly helped by the Merdeka Curriculum seminar.Keywords-Teacher Understanding, Alur Tujuan Pembelajaran (ATP), Merdeka Curriculum.